2007
DOI: 10.1128/aem.00586-07
|View full text |Cite
|
Sign up to set email alerts
|

Novel Whole-Cell Antibiotic Biosensors for Compound Discovery

Abstract: Cells containing reporters which are specifically induced via selected promoters are used in pharmaceutical drug discovery and in environmental biology. They are used in screening for novel drug candidates and in the detection of bioactive compounds in environmental samples. In this study, we generated and validated a set of five Bacillus subtilis promoters fused to the firefly luciferase reporter gene suitable for cell-based screening, enabling the as yet most-comprehensive high-throughput diagnosis of antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 34 publications
4
113
0
Order By: Relevance
“…Similar promoter-lux systems have been used to study the multiple effects of subinhibitory levels of antibiotics, individually or in combination, on gene expression in Salmonella typhimurium and S. aureus; 14,[17][18][19]23 the sensitive and specific nature of transcription responses to bioactive compounds make them useful as a convenient and robust whole-cell screening system for antimicrobials. The light response readout of a lux-based system has an advantage over firefly luciferase (luc) or b-galactosidase (lacZ) reporter systems for this purpose [35][36][37] in that additional substrates are not required for the assay. Promoter-reporters have been used for the discovery of antimicrobials active against Bacillus subtilis 20,35,36,38 and E. coli, 37,39-41 but not against S. aureus until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar promoter-lux systems have been used to study the multiple effects of subinhibitory levels of antibiotics, individually or in combination, on gene expression in Salmonella typhimurium and S. aureus; 14,[17][18][19]23 the sensitive and specific nature of transcription responses to bioactive compounds make them useful as a convenient and robust whole-cell screening system for antimicrobials. The light response readout of a lux-based system has an advantage over firefly luciferase (luc) or b-galactosidase (lacZ) reporter systems for this purpose [35][36][37] in that additional substrates are not required for the assay. Promoter-reporters have been used for the discovery of antimicrobials active against Bacillus subtilis 20,35,36,38 and E. coli, 37,39-41 but not against S. aureus until now.…”
Section: Discussionmentioning
confidence: 99%
“…The light response readout of a lux-based system has an advantage over firefly luciferase (luc) or b-galactosidase (lacZ) reporter systems for this purpose [35][36][37] in that additional substrates are not required for the assay. Promoter-reporters have been used for the discovery of antimicrobials active against Bacillus subtilis 20,35,36,38 and E. coli, 37,39-41 but not against S. aureus until now.…”
Section: Discussionmentioning
confidence: 99%
“…Reporter genes in B. subtilis were used to determine the pathway affected by the compounds, and it was found that the yorB promoter and RecA protein were both induced; indicative of direct interference with DNA structure, synthesis or processing. 33,34 It was also observed that only the atropisomeric products with negative ω C6ʹ,C7ʹ,C7,C8 dihedral angles, namely 12, 14, and 16, exhibited induction of these proteins. Additionally, phenotypic analysis of cells treated with 12, 14, and 16 showed elongated rod-like cells; an indicator for the induction of the bacterial SOS pathway in response to DNA interference.…”
Section: Flavomannins and Talaromannins: Potential Novel Route For Anmentioning
confidence: 96%
“…Bacillus subtilis with luciferase reporter gene is useful in detects compounds that inhibit biosynthetic pathways of bacteria and are compatible with high-throughput screening. This antiBacillus subtilis platform was evaluated against 14,000 natural products with the capability of detects a new action mechanism of the antibiotic ferrimycin A1 [7]. Also this method can monitor metabolite production, as mevalonate that is present in the isoprenoid biosynthesis and can be identified using GFP as reporter, with the end of detect environmental strains with potential of metabolite synthesis [121,122].…”
Section: Antimicrobial Drug Prospectingmentioning
confidence: 99%
“…In this way, biosensors defined as an analytical device that incorporates biological detecting elements known as bioreceptors integrated with a physical transducer are an important approach to measure microbial cell reporters that can be compatible with High-Throughput Screening (HTS) techniques ( Figure 1) [7]. Being classified by bioreceptors in enzymes, microorganisms, antibodies, tissue, organelles and chemoreceptors.…”
Section: Introductionmentioning
confidence: 99%